Cell signaling : principles and mechanisms - Lim, Wendell; Mayer, Bruce; Pawson, T (New York : Garland Science, Taylor & Francis Group, 2015)
'Cell Signaling presents the principles and components that underlie all known signaling mechanisms. The book provides undergraduate and graduate biology students with the tools needed to make sense of the array of specific pathways used by the cell to communicate. As each concept is explained, numerous examples derived from known signaling mechanisms are used to illustrate the key points. It describes basic signaling mechanisms such as protein interactions, changes in enzyme activity, post-translational modifications, subcellular localization of signaling molecules, and small diffusible signaling mediators. The book also explores the components of signaling pathways and how they are'wired' into pathways and circuits that can process information. The book concludes with a unique chapter that presents extended examples in which specific problems encountered in signaling are introduced and solved, followed by a chapter on methods'--
Introduction to cell signaling -- Principles and mechanisms of protein interactions -- Signaling enzymes and their allosteric regulation -- Role of post-translational modifications in signaling -- Subcellular localization of signaling molecules -- Second messengers: small signaling mediators -- Membranes, lipids, and enzymes that modify them -- Information transfer across the membrane -- Regulated protein degradation -- Modular architecture and evolution of signaling proteins -- Information processing by signaling devices and networks -- How cells make decisions -- Methods for studying signaling proteins and networks.
Includes bibliographical references and index.
Keywords: Cellular signal transduction; Cell interaction